The reality of total quality management in educational institutions and its role in achieving excellence performance - Oglah Ali, Ikhlas Satar; Ismeel, Aesar Hassan (Journal of Economics and Administrative Sciences, 2021)
This study is concerned with the reality of total quality management and its role in achieving the excellence performance of the employees of the Institute of Technology / Baghdad, excellence performance is described by the extent to which the organization is able to invest the effort of the human resource to achieve its Objectives by adopting the principles of Total Quality Management (TQM) according to some of its basic dimensions in proportion to the reality and Possibilities Institute, the aim is to study to know the reality of total quality management ,and indicate the levels of excellence performance in the Institute of Technology / Baghdad, And to determine the extent to which there is a fundamental relationship between Total Quality Management and excellence performance and at the level of dimensions, As a refereed questionnaire was distributed to (75) members of the Quality Assurance and University Performance Committees at the Institute, The questionnaire included the main variables of the study (Total Quality Management, excellence Performance) and three sub-dimensions for each variable. The results of the study also indicated a decrease in the degree of interest of the institute understudy for the desires and requirements of the internal and external customer both, despite the interest of the highest management in documenting these requirements and needs, and the capacity to meet it. While the study concluded with weak senior management to adopt strategies or modern philosophies for the purpose of advancing the institute’s reality, and The most important recommendation of the study is the necessity to adopt senior management in the institute strategies adapted to the reality of educational institutions in Iraq, and that helps to apply important concepts and philosophies, such as the concept of Total Quality Management, which is the best way to achieve excellence performance, and to introduce new and more aspirational blood capable of taking bold decisions in adopting the principles Total quality management with the conservatism and using the institute’s open expertise and capabilities